2012
DOI: 10.1016/j.oooo.2011.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Effect of basic fibroblast growth factor on root resorption after delayed autotransplantation of tooth in dogs

Abstract: Objectives. To investigate the effect of basic fibroblast growth factor (FGF-2) on root resorption following delayed autotransplantation in dog.Study design. Mandibular second and third premolars of beagle dogs were extracted to create sites for autotransplantation. After two months, in the experimental sites, the first and fourth mandibular premolars were extracted and air-dried prior to autotransplantation with the application of recombinant FGF-2, while control sites received teeth without FGF-2. At 2, 4, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
1
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 45 publications
0
21
1
2
Order By: Relevance
“…Moreover, in the present study, the application of FGF-2 did not completely prevent replacement resorption, and more instances of ankylosis were observed in roots treated with FGF-2 than has been reported in other experiments [ 21 22 ]. Nonetheless, the results of this study clearly show that FGF-2 stimulates adjacent PDL tissue on the root surface and exerts a positive influence on the regeneration of the PDL and cementum.…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…Moreover, in the present study, the application of FGF-2 did not completely prevent replacement resorption, and more instances of ankylosis were observed in roots treated with FGF-2 than has been reported in other experiments [ 21 22 ]. Nonetheless, the results of this study clearly show that FGF-2 stimulates adjacent PDL tissue on the root surface and exerts a positive influence on the regeneration of the PDL and cementum.…”
Section: Discussioncontrasting
confidence: 77%
“…Seshima et al [ 21 ] reported that the incidence of ankylosis in their FGF-2 treatment group was significantly lower than in the control group (3.6%±4.0% of total root length versus 25.4%±1.0% of total root length; P <0.01) at eight weeks after surgery. Shiratani et al [ 22 ] reported that roots treated with FGF-2 exhibited the formation of new PDL-like tissue and new cementum with inserting collagen fibers after delayed transplantation, and Sato et al [ 23 ] reported that teeth treated with 1 µg of basic FGF in collagen gel exhibited the formation of dense fibers bound to alveolar bone and new cementum at eight weeks. Similarly, the histomorphometric analysis conducted in the present study showed that the amount of replacement resorption in the FGF-2-treated group was less than in the negative control group at four and eight weeks (four weeks, 34.7%±11.0% of the denuded surface of the roots versus 65.8%±27.8% of the denuded surface of the roots; eight weeks, 36.9%±30.0% of the denuded surface of the roots versus 72.1%±22.7% of the denuded surface of roots).…”
Section: Discussionmentioning
confidence: 99%
“…Dört ve sekizinci haftalarda, replasman kök rezorpsiyonunun kontrol grubunda anlamlı şekilde yüksek olduğu vurgulanmış, FGF-2 nin periodontal dokunun hasarlandığı durumlarda replasman rezorpsiyonunu önleyebileceği bildirilmiştir. 42 …”
Section: Prognostik Faktörler Ve Kök Rezorpsiyonuunclassified
“…The occurrence of replacement resorption in the bFGF treated group was significantly lower than in the control group. They concluded that topical application of bFGF reduced the occurrence of ankylosis and root resorption after delayed auto transplantation [ 27 ]. Furthermore, other researchers reported that the replantation of teeth in monkeys in sockets filled with bFGF, with or without fibrin glue, showed higher occurrence of healing in the bFGF/fibrin glue group.…”
Section: Recent Developments On Root Surface Modalities In Delayed Rementioning
confidence: 99%